ANALISIS PUTUSAN PEMBATALAN PERJANJIAN PERDAMAIAN HOMOLOGASI PADA KASUS KEPAILITAN PT NJONJA MENEER (STUDI KASUS: PUTUSAN PENGADILAN NIAGA SEMARANG NOMOR 11/PDT.SUS-PAILIT/2017/PN NIAGA SMG. JO. PUTUSAN MAHKAMAH AGUNG NOMOR 1397 K/PDT.SUS-PAILIT/2017). - Indah Jacinda; Stanislaus Atalim (Fakultas Hukum Universitas Tarumanagara, 2019)
A form of reconciliation in Suspension of Payment is an agreed composition plan, and the composition plan must get the court’s ratification (homologation). According to Article 170 of the Bankruptcy Law number 37/2004, the creditor can request the cancellation of the composition plan that has been approved if the debtor fails (negligent) to fulfill their obligations. Furthermore, in Article 291 Paragraph 2 of the Bankruptcy Law states that if the cancellation is approved, the debtor must be declared bankrupt. And in this case, PT Njonja Meneer was declared bankrupt because they were considered negligent in fulfilling their obligation according to the composition plan, which if we look in Indonesian Civil Code, on Article 1238 it’s stated that someone can only be said to be negligent if they do not carry out their obligations after the due date and have received a notice beforehand. And in this case, the composition plan’s due year is still in 2020 but in 2017, the debtor has already called negligent and declared bankrupt by the court. Therefore, while the research methods in this journal use normative research methods supported by interview data, this journal will examine further about the composition plan itself and the term of negligent in fulfilling the obligations according to the bankruptcy law.